Canva application training to support teaching at Kindergarten Tunas Rimba 1, Samarinda - Rony Herman; Dwi Cahyadi (Community Empowerment, 2023)
Teacher competence, especially in the field of digital technology and the development of teaching materials for early childhood education, is very much needed at this time. Tunas Rimba 1 Kindergarten teachers are required to try to find opportunities to take part in training both organized by the government and the private sector. For the Samarinda State Polytechnic Design Department, it is important to provide additional skills regarding the use of digital technology to Tunas Rimba 1 Samarinda Kindergarten teachers to support their teaching. In this case, use the Canva application to create teaching materials that can be presented both visually and audioly so that young children will easily like them. The method of implementing the training begins with an introduction to Canva, practicing the application of Canva in learning, giving assignments and evaluating the designs made by kindergarten teachers. From the results of the Canva design application training activities to support teaching for Tunas Rimba 1 Kindergarten Teachers in Samarinda, it showed a significant improvement, marked by the high level of positive and enthusiastic responses from participants towards the training.